Enhancing Students' Reading Comprehension In Descriptive Text Through Directed Reading Thinking Activity (DRTA): A Classroom Action Research At The Tenth Grade Of SMA Negeri 6 Padangsidimpuan - Hutapea, Mutiara Cindy Tesalonika; Harputra , Yuswin; Harahap, Tinur Rahmawati (Yayasan Kajian Riset dan Pengembangan RADISI, 2025)
This research investigates the effectiveness of Directed Reading Thinking Activity (DRTA) in enhancing reading comprehension of descriptive texts among tenth-grade students at SMA Negeri 6 Padangsidimpuan. Using classroom action research with 32 students from Class X-1, the study implemented DRTA through a systematic approach of prediction, verification, and reflection. Initial assessment showed only 15.625% of students achieving scores above the Minimum Competency Criteria (KKM) of 75. Findings demonstrate significant improvement, with average scores increasing from 56.56 in pre-cycle to 71.91 in Cycle I and 83.34 in Cycle II. The percentage of students reaching KKM rose to 90.625% after Cycle II. DRTA effectively transformed reading into an interactive process, addressing key challenges of vocabulary deficiencies and low engagement. The findings highlight the importance of student-centered approaches in EFL reading instruction.